2005
DOI: 10.1590/s0103-50532005000500017
|View full text |Cite
|
Sign up to set email alerts
|

Structural impact of hydroxyvalerate in polyhydroxyalkanoates (PHAscl) dense film monitored by XPS and photothermal methods

Abstract: Filmes densos de poli(3-hidrobutirato) e poli(3-hidroxibutirato-co-3-hidroxivalerato) com espessuras de 90 µm foram obtidos utilizando o método "casting" de deposição e caracterizados por espectroscopia de fotoelétrons, calorimetria diferencial e métodos fotoacústicos. As frações molares de hidroxivalerato utilizadas foram de 8, 14 e 22 % molar. Seguindo uma mesma tendência, a capacidade térmica específica e a temperatura de transição vítrea diminuem com o aumento da concentração de hidroxivalerato.Poly(3-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…As expected, an increase in C1 proportion was observed with the increase in PHO content in PHB/PHO due to the Three peaks were detected in all PHB films: the peak at 284.7 eV (C1), attributed to carbon in hydrocarbons (C-C, C-H), the peak at 286.3 eV (C2), associated with the ether bond (C-O), and the peak at higher binding energy, 288.6 eV (C3), corresponding to the carbonyl (C=O) bond. The values of binding energies of these carbon species are in good agreement with the ones found in the literature [44,45]. Based on the proportion of these carbon species, the surface concentration of the different chemical bonds was calculated and the results are given in Table 4.…”
Section: Surface Properties By X-ray Photoelectron Spectroscopysupporting
confidence: 86%
“…As expected, an increase in C1 proportion was observed with the increase in PHO content in PHB/PHO due to the Three peaks were detected in all PHB films: the peak at 284.7 eV (C1), attributed to carbon in hydrocarbons (C-C, C-H), the peak at 286.3 eV (C2), associated with the ether bond (C-O), and the peak at higher binding energy, 288.6 eV (C3), corresponding to the carbonyl (C=O) bond. The values of binding energies of these carbon species are in good agreement with the ones found in the literature [44,45]. Based on the proportion of these carbon species, the surface concentration of the different chemical bonds was calculated and the results are given in Table 4.…”
Section: Surface Properties By X-ray Photoelectron Spectroscopysupporting
confidence: 86%
“…On the other hand, PHA films exhibited a T g at −4.7 °C, whereas PLA showed a marked transition at 58.1 °C (Figure 1c). Glass-transition temperatures ranging from 2.7 to −4.4 °C for a PHA matrix obtained by casting were reported by da Silva et al 22 The thermograms of all the mixtures exhibited PLArecrystallization peaks at 107 °C; this transition was more evident with higher PLA proportions in the mixture (Figure 1a). These results indicate that the incorporation of PHA contributes to the process of recrystallization of PLA in all the blend formulations.…”
Section: Journal Of Agricultural and Food Chemistrysupporting
confidence: 71%
“…On the other hand, PHA films exhibited a T g at −4.7 °C, whereas PLA showed a marked transition at 58.1 °C (Figure c). Glass-transition temperatures ranging from 2.7 to −4.4 °C for a PHA matrix obtained by casting were reported by da Silva et al…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this results in increasing the processing temperature window and maintaining degradation rates within acceptable limits. 154,188,[193][194][195][196] In their studies, 178,197 the authors reported a drop in the T m for PHB from 176 C to 158 C with 22 wt% HV content. In another study, the same drop in the melting temperature was obtained with only 8 wt% HV content.…”
Section: Phas' Physical and Thermal Propertiesmentioning
confidence: 99%